2023
DOI: 10.3390/agronomy13020415
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differential-Expressed Genes in Banana-Biostimulant Interaction Using Suppression Subtractive Hybridization

Abstract: The use of environmental-friendly agricultural inputs to increase yield in crops could reduce environmental contamination and alleviate (a)biotic stress. In this study, we applied a foliar liquid biostimulant to banana plants, which was developed from the anaerobic fermentation of microorganisms with organic remains (manure and plant waste) and minerals to use as environmental-friendly product. To determine the effect of this biostimulant in the plants, a Suppression Subtractive Hybridization (SSH) library was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…It appears that no elicitor effect of Musa leachate on tomato has been reported in the literature to date. However, our results are consistent with a previous study where anaerobic fermentation of manure and plant waste (containing humic substances) stimulated salicylic and jasmonic pathways in banana cultivar [50]. Another study showed that fulvic acid regulates phenylpropanoid metabolism in grapefruit [51].…”
Section: Paradisiaca Leachate As a Plant Defense Elicitorsupporting
confidence: 93%
“…It appears that no elicitor effect of Musa leachate on tomato has been reported in the literature to date. However, our results are consistent with a previous study where anaerobic fermentation of manure and plant waste (containing humic substances) stimulated salicylic and jasmonic pathways in banana cultivar [50]. Another study showed that fulvic acid regulates phenylpropanoid metabolism in grapefruit [51].…”
Section: Paradisiaca Leachate As a Plant Defense Elicitorsupporting
confidence: 93%